Basic Information of the Journal - Apex College, (Apex Journal of Business and Management, 2025)
Apex Journal of Business and Management is an academic, not for profit, blind peer-reviewed journal of business and social sciences across managerial disciplines. It aims to provide professors, scholars, managers, academicians, scientists, industrial professionals, researchers, students and learned members of the community from all over the world an authentic open-access platform featuring scholarly research, reviews and perspectives on the state of current research on topics of interdisciplinary interest. The AJBM bi-annual journal is published both in print and electronic forms in the month of September and March of every year. It is an unique journal published from Nepal.